2017
DOI: 10.1080/14763141.2017.1391323
|View full text |Cite
|
Sign up to set email alerts
|

Power and pacing calculations based on real-time locating data from a cross-country skiing sprint race

Abstract: Pacing strategies in cross-country skiing have been investigated in several studies. However, none of the previous studies have been verified by collected skiing data giving the skiing velocities along a measured track. These can be used to calculate the propulsive power output. Collected real-time positioning data from a cross-country sprint skiing race were used to estimate the propulsive power by applying a power balance model. Analyses were made for the time-trial and the final for one female and one male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 22 publications
0
34
2
Order By: Relevance
“…In the only comparison of sprint skiing by males and females known to us, Swarén and Eriksson 7 found that in the first 20 m of the final race, the average propulsive power for the 1 female skier analyzed was 11% higher than in the qualification heat (345 W vs. 308 W, respectively), whereas for the 1 male skier this power was 17% lower (356 W vs. 430 W, respectively). The pattern for the final spurt was the same, with higher values than in the qualification heat for the female (380 W vs. 361 W, respectively), and lower for the male (411 W vs. 475 W, respectively).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…In the only comparison of sprint skiing by males and females known to us, Swarén and Eriksson 7 found that in the first 20 m of the final race, the average propulsive power for the 1 female skier analyzed was 11% higher than in the qualification heat (345 W vs. 308 W, respectively), whereas for the 1 male skier this power was 17% lower (356 W vs. 430 W, respectively). The pattern for the final spurt was the same, with higher values than in the qualification heat for the female (380 W vs. 361 W, respectively), and lower for the male (411 W vs. 475 W, respectively).…”
Section: Resultsmentioning
confidence: 89%
“…sprint race Skating Male 12 elite XC sprint skiers (VO 2max : 70.0 mL/min/kg; F.I.S. sprint points: 44.1) 2D video analysis (10 synchronized cameras; section times) on a specific uphill section; no wind, with stable air and snow temperature –4°C and relative humidity 75% Swarén and Eriksson 7 1400 m, qualification time trial & 3 heats during the Scandinavian Cup Classic Female and male 2 elite XC skiers Continuous monitoring of the position of the skiers by the Quuppa real-time locating system (50 Hz) Distance races Norman and Komi 19 15 km Classic Male 7 of the top 10 finishers and 4 of the skiers who placed 30th–60th in the 15 km 1978 Lahti World Championships 2D video analysis uphill, split times Norman et al 26 30 km Classic Male The first 5 ranked and all Canadian and American skiers in the 30 km 1988 Calgary Winter Olympics 2D video analysis uphill, split times Bilodeau et al 25 30 km/50 km Skating & classic Male Members of the Canadian National XCS Training Centers and International elite racers 2D video analysis uphill, split times, HR; snow temperature –1.0°C to –0.5°C, air temperature 1°C–4.9°C Rundell and McCarthy 24 10 km Skating Female Top US XC skiers 2D video analysis; air temperature –17°C Welde et al 22 6.2 km/6.2 km Classic & skating Female High-level female XC skiers (VO 2max : 67 mL/min/kg) Ergospirometry, blood lactate concentration, HR; no wind, air temperature 2°C–6°C Bolger et al 20 10 km/15 km Classic & skating Female and male Norwegian XCS National Team (VO 2max : 81.7 and 71.0 mL/min/kg for male and female, respectively; F.I.S. Points 4.0 and 8.0, respectively) Low-cost GNSS c...…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances in wearable sensor technology allow tracking of athletes as a point mass model for position, speed, and acceleration, by using a differential global navigational satellite system (dGNSS), during outdoor roller skiing ( Larsson and Henriksson-Larsen, 2005 ; Andersson et al, 2010 ). Using this wearable technology, the external work load can be determined ( Swaren and Eriksson, 2017 ) and the metabolic cost of roller ski racing can be estimated to illustrate the exercise intensity during a race.…”
Section: Introductionmentioning
confidence: 99%
“…Video-based tracking is only applicable if the athletes are in the field of view of a camcorder throughout the race and are therefore not often used in racing and endurance sports. LPS is typically used for indoor sports but can also be used in outdoor sports that are held in limited space, such as on track loops ( Self et al, 2012 ; Swarén et al, 2016 ; Swarén and Eriksson, 2017 ). GNSS does not have the two limitations described above and is therefore the most commonly applied wearable technology used to track athletes in outdoor sports.…”
Section: Introductionmentioning
confidence: 99%